Influence of Some Growth Conditions on The Antibacterial Activities of Lactobacillus fermentum Against Human Fecal Staphylococcus aureus - Nguyễn Anh, Dũng (Hasanuddin University, 2023)
One of the best-known and widespread bacterial pathogens that cause invasive infections as well as skin infections is recognized as Staphylococcus aureus strains to contribute to certain pneumonia and other respiratory tract infections, cardiovascular infections, infections at surgical sites, infections of prosthetic joints, and nosocomial bacteremia. Meanwhile, Lactic acid bacteria (LAB) have an effective antibacterial potential that may be used to safeguard both human and animal health, according to several research. Numerous LAB strains are side effect free and incapable of harming both people and lab animals. Hence, this study was performed to investigate the optimal conditions including MipH, InTe, and InTi for Lactobacillus fermentum (LAF) isolated from traditional fermented foods against human fecal Staphylococcus aureus (hf-SA).